2020
DOI: 10.1186/s40659-020-00300-8
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents neuronal loss and structural changes in the superior cervical (sympathetic) ganglion induced by chronic sleep deprivation, in the rat model

Abstract: Background: In modern societies, sleep deprivation is a serious health problem. This problem could be induced by a variety of reasons, including lifestyle habits or neurological disorders. Chronic sleep deprivation (CSD) could have complex biological consequences, such as changes in neural autonomic control, increased oxidative stress, and inflammatory responses. The superior cervical ganglion (SCG) is an important sympathetic component of the autonomic nervous system. CSD can lead to a wide range of neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The rats in the other groups were placed in a water tank with multiple platforms for 21 days to induce chronic sleep deprivation (CSD), according to the Erfanizadeh's method. 26…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rats in the other groups were placed in a water tank with multiple platforms for 21 days to induce chronic sleep deprivation (CSD), according to the Erfanizadeh's method. 26…”
Section: Methodsmentioning
confidence: 99%
“…The rats in the other groups were placed in a water tank with multiple platforms for 21 days to induce chronic sleep deprivation (CSD), according to the Erfanizadeh's method. 26 Rats in the positive control group received 0.18 mg kg −1 Estazolam tablets and those in the PCWP group received 100 mg kg −1 PCWP. Estazolam tablets and PCWP extract were dissolved in pure water.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…A decrease in apoptosis was observed in all curcumin-applied control groups. As a result, it has been reported that the harmful effects of sleep deprivation can be prevented by curcumin-administered orally [ 141 ].…”
Section: Role Of Curcumin In Sleep Disorders and Alzheimer's Disease:...mentioning
confidence: 99%
“…Although there are few studies on sleep deprivation with curcumin, the ones that have been done show that when given during sleep deprivation, antioxidant effective curcumin prevents platform sleep deprivation neuron loss in the rat cortices. However, only one research used stereological methods to assess cell loss [ 141 ]. Studies reported that sleep deprivation increases oxidative stress or that curcumin decreased oxidative stress in animals protected from sleep loss neural injury.…”
Section: Role Of Curcumin In Sleep Disorders and Alzheimer's Disease:...mentioning
confidence: 99%
“…[19] The research has shown that the disturbed sleep-wake cycle (SD) has generated a DNA desecration response and neuronal death, crushing the neuronal augmentation, and decreasing the hippocampal gliogenesis and dendritic spines and length in different parts of the brain. [20] Sleep deprivation has known to be a destroyer of a variety of brain malfunctions, along with the reason of improper function of memory, depression, and psychosis. [19] Turmeric divides itself into three parts as known as far as curcumin, demethoxycurcumin, and in bisdemethoxycurcumin controlling the effect of inflammation, cell growth, and apoptosis.…”
Section: Significance Of Curcumin On Rem Sleep With the Explanation O...mentioning
confidence: 99%